Severe ileocecal inflammatory syndrome in adult patients with cystic fibrosis - Henker, Robert; Oltmanns, Annett; Wald, Alexandra; Tuennemann, Jan; Opitz, Sabine; Hoffmeister, Albrecht; Wirtz, Hubert; Mössner, Joachim; Jansen-Winkeln, Boris; Karlas, Thomas (Zeitschrift für Gastroenterologie, 2019)
The relevance of gastrointestinal manifestations of cystic fibrosis (CF) is increasing due to an improved life expectancy. We report on 2 adult patients with prior lung transplantation who presented with a severe inflammatory disorder of the ileocecal region. One patient underwent ileocecal resection; the second patient died after emergency surgery for intestinal perforation. Both cases did not show typical signs of CF-related distal intestinal obstruction syndrome or extensive fibrosing colonopathy. However, the clinical and histopathological findings revealed CF-induced inflammatory alterations of the intestinal mucosa. Thus, these cases illustrate a further CF-related bowel disorder, which can be especially relevant in long-term CF survivors.
Keywords: CF; fibrosing colonopathy; immunosuppression; lung transplantation pancreatin supplementation